2005
DOI: 10.1093/jnci/dji005
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Genotype, Antidepressant Use, and Tamoxifen Metabolism During Adjuvant Breast Cancer Treatment

Abstract: Interactions between CYP2D6 polymorphisms and coadministered antidepressants and other drugs that are CYP2D6 inhibitors may be associated with altered tamoxifen activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
691
3
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 838 publications
(739 citation statements)
references
References 32 publications
25
691
3
17
Order By: Relevance
“…Antidepressants, in particular paroxetine and fluoxetine, known to be potent CYP2D6 inhibitors, are commonly prescribed with tamoxifen in the treatment of hot flashes or depression. 15 However, in Italy, antidepressants are not commonly prescribed for management of hot flashes, and our data show that the overall prevalence of these drugs in the trial was below 1% (data on file). Nevertheless, the effect of CYP2D6 inhibitors on the clinical outcomes cannot specifically be addressed in this study.…”
Section: Serrano Et Almentioning
confidence: 71%
See 3 more Smart Citations
“…Antidepressants, in particular paroxetine and fluoxetine, known to be potent CYP2D6 inhibitors, are commonly prescribed with tamoxifen in the treatment of hot flashes or depression. 15 However, in Italy, antidepressants are not commonly prescribed for management of hot flashes, and our data show that the overall prevalence of these drugs in the trial was below 1% (data on file). Nevertheless, the effect of CYP2D6 inhibitors on the clinical outcomes cannot specifically be addressed in this study.…”
Section: Serrano Et Almentioning
confidence: 71%
“…It has also been reported that SULT1A1 may influence tamoxifen metabolites' concentration. 29,42,43 However, previous studies 15,29 have not shown significant associations between SULT1A1 genotypes and the serum levels of 4OH-tamoxifen or endoxifen per se. Our results did not show any differences between SULT1A1 genotype and BC risk, suggesting that SULT1A1 may not be important in explaining tamoxifen preventive efficacy.…”
Section: Serrano Et Almentioning
confidence: 92%
See 2 more Smart Citations
“…CYP2D6 is the key enzyme metabolizing the pro-drug tamoxifen into its metabolites 4-hydroxy tamoxifen, 4-desmetyl tamoxifen and its most active metabolite, endoxifen [13,14]. The CYP1A2 and CYP2C8 enzymes also contribute to tamoxifen metabolism [15,16] as well as the metabolism of caffeine [17], while SULT1A1 has been proposed to be involved in sulfation of 4-hydroxytamoxifen and may also play a role in endoxifen clearance [13].…”
Section: Introductionmentioning
confidence: 99%